Disposal practice for unused medications among the students of the International Islamic University Malaysia - Azad, Md. Abdul Kalam; Md. Akhtaruzzaman Akhter, Md. Rezaul Haque Ansary; Al-Mamun, S. M.Mostofa; Uddin, Mohi; Rahman, Md. Mokhlesur (Journal of Applied Pharmaceutical Science (http://www.japsonline.com), 2012)
This survey has lead to an enhanced international awareness of the potential detrimental effects on the environment. The main objective of this survey is to develop of public awareness about harmful effect of medications waste.This was a descriptive crosssectional survey involving with patients based on a structured questionnaire format with answer sets and asked why people do not use all of their medications; why they are keep unused medications, storage and how to dispose their medications. This study carried out at International Islamic University Malaysia (Health center Gombak campus, Selangor) and the medical college of the International Islamic University Malaysia (kuantan campus, Pahang). Although,87% of the respondents; they known about medications waste but only near about 2% of the respondents who are follow drug-take-back system because of above 93% of the respondents, they did not know about drug-take-back system. Most of the participants reported disposing of these in a manner that leads to their ending up in a landfill more than 65%. Finally, 83% of the respondents added to a disposal system ultimately ending up in a landfill. In this survey suggests that there is an urgent need to develop of public awareness and there is also need to develop dispensing policies & delivered to collection bag which deduction the volume of medication waste.